Pengaruh Kompensasi dan Disiplin Kerja terhadap Kepuasan Kerja Karyawan - Tiyan Widiyanto; Rianti Setyawasih (Fakultas Ekonomi Universitas Islam 45, 2019)
Employee satisfaction can improve organizational performance. There are various factors that can influence employee satisfaction, such as compensation and work discipline. This study purposed to analyze the effect of compensation and work discipline on job satisfaction at PT Pos Indonesia (Persero) in Bekasi. There are 150 permanent employees at PT Pos Indonesia (Persero) in Bekasi that used as a population. The study was carried out in 2019 on a convenience sample of 109 respondents. The data analysis used statistical tests with Statistical Product and Service Solutions (SPSS) 23 program. This research model used multiple regression analysis. The results showed that compensation and work discipline had significant effect on job satisfaction at PT Pos Indonesia (Persero) in Bekasi.